Red meat marketing systems in Turkey - Günes T. (Filière des viandes rouges dans les pays méditerranéens, 1998)
Domestic production of red meat was enough for consumption up to recent years. Imports started in the 1990's. The carcass weight is quite low because of the high percentage of native races in livestock population. About 65 per cent of total red meat production is beef. The per capita red meat consumption is around 22 kg. A large number of people and institutions participate in the red meat marketing channel. However 45-50 per cent of total slaughtering is accomplished in an uncontrolled way in those areas where there are no slaughterhouses and in rural areas. Approximately 50 per cent of the retail price goes to producers due to the large number of middlemen participating in the marketing channel and high marketing costs. There are approximately 900 slaughterhouses with a total capacity of 2 million tons. This capacity covers 50-55 per cent of total slaughtering.
Séminaire International sur la Filière des Viandes Rouges dans les Pays Méditerranéens, 20-23 Apr 1997, Tunis (Tunisia)